Development of linear programming model for profitable production of Shornur Agricultural Implements Consortium (P) Ltd. (SAICO) a case study - FATHIMA M.K JAISON MATHEW JOHN; Er. Sindhu Bhaskar (Tavanur 2013 Department of Farm Power, Machinery and Energy)
Development of linear programming model for profitable production of Shornur Agricultural Implements Consortium (P) Ltd. (SAICO) a case study
Development of linear programming model for profitable production of Shornur Agricultural Implements Consortium (P) Ltd. (SAICO) a case study